A structural evidence of polar clusters in PLZT relaxor ceramics. Issue 174 (1st September 2016) - Botero, Eriton Rodrigo; de Azevedo, Douglas Henrique Marcelino; Eiras, José Antônio; Milton, Flavio Paulo; Garcia, Ducinei
ABSTRACT: In this paper, a quantification of the polar/non-polar phases of perovskite single-phase relaxor ferroelectric ceramics of lanthanum modified lead titanate zirconate (PLZT x/65/35, x = 5, 8, 9 and 10%) was performed by Rietveld refinement using measurements obtained with Cu kα radiation and with high-resolution synchrotron radiation. The refinements were performed concerning two crystalline phases, being one of them nonpolar (Pm-3m) and the other polar. The refinement results showed the relationship between the polar/nonpolar phases and the La content in PLZT, suggesting the existence of polar clusters of relaxor ferroelectric ceramics.